Leadership of historically black colleges and universities : a what not to do guide for HBCU leaders - Jones, Johnny D. (Great debates in higher education., 2020)
"Historically Black Colleges and Universities (HBCUs) face critical challenges of funding, accreditation, enrollment, recruitment, retention, and graduation rates, and these have become a staple of smaller colleges in the global competitive marketplace and current higher education system. Offering a comprehensive'what not to do'guide, this book puts forward the past mistakes which leaders must learn from in order to ensure their institution's future. Johnny D. Jones has written this book to arm stakeholders in the academic communities of HBCUs to future-proof how students learn, how faculty teach, and how campuses embrace innovation. Including descriptive case studies, this book empowers readers to navigate their own path to quality leadership. By equipping leaders to identify how future studies can be institutionalized at HCBUs in a way that also compliments historic campus culture, environment, climate, and ecology, Jones sets out a strategy to refine HBCU leadership, which accounts for the specific needs that exist across HBCUs. Serving up practical guidance and best practice advice, Johnny's book is essential reading for researchers and academic leaders across the US who wish to ensure that these exceptional schools not only survive, but thrive."--Publisher.